Management of asymptomatic hyperuricemia in chronic kidney disease: A proposed stepwise approach - Mohammed Abdel Gawad,; Zaki, Dina; Qasem, Anass (African Journal of Nephrology, 2022)
Serum uric acid levels are frequently elevated in patients with chronic kidney disease (CKD). The relatively modest hyperuricaemia in CKD may reflect the reduced efficiency of renal excretion of urate. In the past two decades, basic research has shown that hyperuricaemia plays a causal role in the progression of CKD through direct renal injury. However, clinical studies have reported conflicting results, hence there is much controversy about the scope of treating asymptomatic hyperuricaemia to prevent or reduce the rate of CKD progression. In this review, we highlight the most recent guidelines and clinical trials that tested the use of urate-lowering therapy in the management of asymptomatic hyperuricaemia in CKD patients.